Changing Caribbean geographies: connections in flora, fauna and patterns of settlement from Indian inheritances. Issue 1 (1st September 2021) - Samaroo, Brinsley
Abstract : There can be no doubt that Indian immigration to the plantation colonies changed the geography of those colonies. However, most analyses have dealt with the sugar industry in the colonies after the abolition of slavery. This paper will argue that, apart from the sugar industry, Indian labour and ingenuity made other significant contributions to plantation economies. The girmityas (agreement signers) were well aware that they were going to agricultural occupations so they took with them an amazing array of dried fruits, seeds and cuttings, which survived the long crossing, adding to the flora of the plantations. Armed with this foreknowledge, the jahajis packed these items into their jahaji bundles alongside the Tulsi Ramayan and the Holy Qu'ran. Animals too formed part of this international trade. Sheep, goats and poultry which were not eaten on the outward voyage were sent to the estates, where they multiplied. When dangerous snakes threatened plantation security, cages of mongoose were dispatched to the Caribbean where they bravely tackled venomous creatures. At the urging of Indian labourers with long experience in the sugar industry, the plantations' owners imported Brahma bulls and Zebu cattle, which revolutionised transport on the estates and provided leather, manure and meat to the wider population. There is also the amazing story of the importation of hundreds of water buffaloes ( bhaisa ) from the Indo-Gangetic plains. Some nine breeds were imported and in the twentieth century Caribbean bio-geneticists were able to blend the best qualities of those Indian animals and created a new hybrid, the buffalypso, which combined the scientific name with Trinidad's fame as the land of the calypso. The buffalypso became a prized animal for haulage, meat, milk and leather and an item of export to Venezuela, Colombia, Miami and the wider Caribbean. Indian cultivars were continuously exported to the botanic gardens in the Caribbean and Indian forestry experts were sent to the region to advise on forest rehabilitation in the wake of large-scale deforestation, which sugar cultivation required. In these and other ways the physical character of the Caribbean underwent permanent change, which manifests itself today.